2010
DOI: 10.1160/th09-06-0416
|View full text |Cite
|
Sign up to set email alerts
|

Expression of tissue factor pathway inhibitor (TFPI) in human breast and colon cancer tissue

Abstract: Activation of blood coagulation, a phenomenon frequently observed in breast and colon cancer patients, contributes to tumour progression. The principal initiator of blood coagulation activation in cancer patients is tissue factor (TF), while tissue factor pathway inhibitor (TFPI) is the main inhibitor of the TF-dependent pathway of blood coagulation. Previous immunohistochemical studies revealed no expression of TFPI in human cancer cells. The aim of the study was to evaluate the expression of TFPI protein and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 39 publications
1
44
0
1
Order By: Relevance
“…However, more recent evidence indicates an additional role of TFPI in cancer. Several cancer tissues and cell lines have been shown to express TFPI [14], [15], and TFPI treatment has been reported to reduce tumor growth and metastasis in vivo [16], [17]. We recently reported that overexpression of TFPIα or TFPIβ in SK-BR-3 breast cancer cells resulted in pro-apoptotic and anti-proliferative effects of either isoform in vitro [18], but the mechanism behind the effect of TFPI is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent evidence indicates an additional role of TFPI in cancer. Several cancer tissues and cell lines have been shown to express TFPI [14], [15], and TFPI treatment has been reported to reduce tumor growth and metastasis in vivo [16], [17]. We recently reported that overexpression of TFPIα or TFPIβ in SK-BR-3 breast cancer cells resulted in pro-apoptotic and anti-proliferative effects of either isoform in vitro [18], but the mechanism behind the effect of TFPI is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In ABC IHC technique the examined antigens were visualized as dark brown reaction products. The expression level of the receptors was measured using semiquantitative scale by Remmale and Stegner in our own modification [25]. Numerical results were grouped by the percentage of stained cells (A) and intensiveness of this staining (B).…”
Section: Methodsmentioning
confidence: 99%
“…TFPI-2 is highly expressed in the placenta, but is also synthesized in various normal tissues, including the endothelial cells of various blood vessels [66] . Previous studies have shown that breast cancer tissues may also synthesize TFPI-1 [67] and TFPI-2 [66] , and TFPI-1 expression levels were correlated with disease malignancy. In keeping with this observation, multiple breast cancer cell lines also express TFPIα and TFPIβ [68] .…”
Section: Tissue Factor Pathway Inhibitors: Negative Regulators Of Tf-mentioning
confidence: 99%